Bleeding Risk, Dual Antiplatelet Therapy Cessation, and Adverse Events After Percutaneous Coronary Intervention: The PARIS Registry. (April 2020) - Sorrentino, Sabato; Sartori, Samantha; Baber, Usman; Claessen, Bimmer E.; Giustino, Gennaro; Chandrasekhar, Jaya; Chandiramani, Rishi; Cohen, David J.; Henry, Timothy D.; Guedeney, Paul; Ariti, Cono; Dangas, George; et al.
Abstract : Background: Whether the underlying risk of bleeding influences the associations between patterns of dual antiplatelet therapy (DAPT) cessation and adverse events after percutaneous coronary intervention is unknown. Methods: Patients enrolled in the prospective, international, multicenter PARIS registry (Patterns of Non-Adherence to Anti-Platelet Regimens in Stented Patients) were categorized according to their risk of bleeding using the PARIS bleeding risk score. We evaluated the incidence, patterns, and association between modes of DAPT cessation and outcomes across bleeding risk groups. Modes of DAPT cessations were defined as physician-guided DAPT discontinuation, brief interruption (<14 days) or disruption for bleeding, or noncompliance. The primary end point of interest was major adverse cardiac events, defined as the composite of cardiac death, myocardial infarction, or definite-probable stent thrombosis. Results: From a total of 5018 patients, 513 (10.2%) were classified as high, 2058 (41.0%) as intermediate, and 2447 (48.8%) as low risk for bleeding. High bleeding risk (HBR) patients were older and had greater prevalence of comorbidities. Compared with non-HBR, HBR patients had higher rates of both ischemic and bleeding events. The cumulative incidence of DAPT cessation was higher in HBR patients, mostly driven by physician-guided discontinuation and disruption. Of note, DAPT disruption occurred in 17.7%, 10.4%, and 7.8% at 1 year and 22.0%, 15.1%, and 12.0% at 2 years ( P <0.0001) in high, intermediate, and low bleeding risk groups, respectively. Physician-guided DAPT discontinuation was not associated with increased risk of major adverse cardiac events in both HBR and non-HBR patients, while DAPT disruption was associated with an increased risk of major adverse cardiac events across all bleeding risk groups. There was no interaction between bleeding risk status and clinical outcomes for any cessation mode. Conclusions: Patients at HBR remain at higher risk of adverse events. Disruption of DAPT is associated with an increased risk of major adverse cardiac events irrespective of the underlying bleeding risk. Physician-guided discontinuation of DAPT appears to be safe, irrespective of HBR. Abstract : Supplemental Digital Content is available in the text.